2009
DOI: 10.3109/17482620903180350
|View full text |Cite
|
Sign up to set email alerts
|

On the outskirts of normality: Young adults with disabilities, their belonging and strategies

Abstract: During the last decades, the living conditions for young people with disabilities have changed dramatically in Sweden, as well as in other parts of the Western world. The boundaries between what is considered normal as opposed to different have become less clear as a result of these changes. This has been followed by new problems regarding integration and changing patterns of marginalization. The aim of this study was to gain a deeper understanding of the ways in which young adults' social identity is shaped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, if the abnormal involves dangerous extremists and anarchists, the normal refers to moral honourable citizens (Yang et al, 2007;Ryan, 2011). More specifically, normality has been studied in terms of stigmatised people (Goffman, 1983), stigmatised countries (Adler-Nissen, 2014), the disabled (Olin & Jansson, 2009), the homeless (Smith, 2011) as well as minority groups and migrants (Ryan, 2010(Ryan, , 2011. A similarity that we find across all of these studies is that those groups who may be described as 'abnormal' or 'not so normal' in relation to a specific community or system, can achieve normality when in their interactions with others show conformity and acceptance of the institutional roles and standards (Goffman, 1961).…”
mentioning
confidence: 99%
“…For example, if the abnormal involves dangerous extremists and anarchists, the normal refers to moral honourable citizens (Yang et al, 2007;Ryan, 2011). More specifically, normality has been studied in terms of stigmatised people (Goffman, 1983), stigmatised countries (Adler-Nissen, 2014), the disabled (Olin & Jansson, 2009), the homeless (Smith, 2011) as well as minority groups and migrants (Ryan, 2010(Ryan, , 2011. A similarity that we find across all of these studies is that those groups who may be described as 'abnormal' or 'not so normal' in relation to a specific community or system, can achieve normality when in their interactions with others show conformity and acceptance of the institutional roles and standards (Goffman, 1961).…”
mentioning
confidence: 99%
“…In this context the functionally impaired may perceive themselves as inferior [23]. Feedback from the social environment affects a person's self-image [24,25] and how the individual relates to others. Disabled individuals have reported that the worst thing about their life is people's expressions of disgust, pity, horror or curiosity and that it can make them hide an impairment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the meaning that places have in young people's recovery appears relevant to pursue in further research. Thirdly, the included studies do not address young people's agency in terms of how they may rebel against identity positions when diagnosed with a mental illness [73]. It appears relevant to pursue these perspectives in further research.…”
Section: Strengths Limitation and Reflections On Research Positionsmentioning
confidence: 99%